The Effect of Psychological Capital as a Mediator of Transformational Leadership on organizational Citizenship Behavior Among Generation Z Employees In Surakarta - Eka Ayu Cindy Anisa Putri; Zandra Dwanita Widodo; Atik Lusia (ProBisnis : Jurnal Manajemen, 2026)
The increasingly dynamic work environment requires organizations to have employees who not only perform formal job duties but also demonstrate extra-role behavior known as Organizational Citizenship Behavior (OCB). Generation Z, which is beginning to dominate the workforce, has distinct psychological characteristics that require an appropriate leadership approach. This study aims to examine the effect of transformational leadership on OCB with psychological capital as a mediating variable among Generation Z employees in Surakarta. This study employs a quantitative approach using a survey method involving 130 Generation Z employees selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with SmartPLS. The results indicate that transformational leadership has a positive and significant effect on psychological capital, and psychological capital has a positive and significant effect on OCB. Furthermore, psychological capital is proven to mediate the relationship between transformational leadership and OCB. These findings highlight the importance of transformational leadership in enhancing psychological capital and encouraging extra-role behavior among Generation Z employees.